The value of urban design a research project commissioned by CABE and DETR to examine the value added by good urban design. (Thomas Telford, 2001)
Good urban design offers strong competitive advantages and does not necessarily cost more to deliver. This ground-breaking report examines the way in which superior urban design adds value by increasing the economic viability of development and by delivering social and environmental benefits.